Billing and Payment of Accounts Receivable Procedures - Putri Cantika (Journal of Applied Accounting and Taxation, 2016)
This research discusses about the billing of accounts receivable procedures to the customer every month and the payment of accounts receivable procedures until the limit time that given by the company. Billing and payment of accounts receivable procedures have their own stages. The problem is often occurs a delay in the payment of accounts receivable by customers due to certain factors. One of factor is receivable collection procedures or billing were not running smoothly so that the invoice does not get to the customers on time. The procedures that interrelated if one step is an obstacles it will have an impact on the increase of unpaid receivables in the company. The Company must pay attention to the performance of the parties associated with the billing and payment of accounts receivable procedures. The Company must also provide solutions so that customers are willing to pay accounts receivable on time to the company every month. The solution, for example by giving discounts to customers who pay off debts on time before the maturity date. Receivables are paid on time would be good for corporate finance. It will also affect the working relationship between the company and the customer.